First report of cucumber mosaic virus in yams (Dioscorea spp.) in Ghana, Togo and Republic of Benin in West Africa - Eni, A.O.; Kumar, L.; Asiedu, Robert; Alabi, O.J.; Naidu, R.A.; Hughes, J.A.; Rey, M.E. (Scientific Societies, 2008)
Yam (Dioscorea spp., family Dioscoreaceae) is one of the most important food crops cultivated in the West African yam zone comprising the forest and savannah areas of Nigeria, Ghana, Côte d'Ivoire, Republic of Benin, and Togo, which account for more than 90% of the 4.59 million ha of yam cultivation worldwide (1). A survey was conducted in 2005 to document viruses in yams in Ghana, Togo, and the Republic of Benin. Samples (1,405) from five species of yam showing mosaic, chlorosis, and stunting as well as asymptomatic plants were tested for Dioscorea bacilliform virus (DBV, genus Badnavirus), Yam mosaic virus (YMV, genus Potyvirus), and Yam mild mosaic virus (YMMV, genus Potyvirus), the three most common viruses infecting yams. In addition, samples were tested for Cucumber mosaic virus (CMV), since CMV was previously reported to infect yams in Côte d'Ivoire (2) and Nigeria (3). In protein-A sandwich-ELISA with polyclonal antibodies to a cowpea isolate of CMV, 23 of the 1,405 samples (6 of 218 samples from Togo, 13 of 628 samples from Ghana, and 4 of 559 samples from Republic of Benin) tested positive for CMV. The CMV-positive samples were from D. alata (N = 16) and D. rotundata (N = 7), whereas all samples from D. cayenensis, D. dumetorum, and D. bulbifera tested negative. CMV was detected as mixed infections with DBV, YMV, or YMMV in 21 of 23 samples. Some of these samples showed puckering, chlorosis, mottling, and crinkling, whereas some plants infected by two or more viruses were asymptomatic. Only two samples from D. rotundata had a single infection of CMV and they showed mild chlorotic symptoms in young leaves that were inconspicuous in mature leaves. In sap inoculations, the virus induced systemic mosaic in Nicotiana glutinosa. The presence of CMV in ELISA-positive yam samples was further confirmed by immunocapture-reverse transcription (IC-RT)-PCR using CMV antibodies as trapping antibody and oligonucleotide primers specific for a 485 nt corresponding to 3′ end of the coat protein gene and C-terminal noncoding region of RNA-3 (4). To confirm the specificity of IC-RT-PCR, the 485-bp amplicons from an isolate from the Republic of Benin was cloned into pCR2.1 (Invitrogen, Carlsbad, CA) and three independent clones were sequenced from both orientations. Pairwise comparison of a consensus sequence (Accession No. EU274471) with corresponding sequences of other CMV isolates deposited in GenBank showed 99% identity at the nucleotide sequence level (Accession No. U22821) and revealed that the CMV isolate from yam belongs to sub-Group IA. To our knowledge, this is the first report of CMV infection in yams (D. alata and D. rotundata) in Ghana, Togo, and the Republic of Benin. Together with a previous documentation of CMV in D. alata and D. trifida in Côte d'Ivoire and Nigeria (2,3), this report adds to existing knowledge on distribution of CMV in yams with implications for yam production and germplasm distribution in the West Africa Region.